ACTN3 R577X and ACE I/D gene variants influence performance in elite sprinters: a multi-cohort study. (December 2016) - Papadimitriou, Ioannis; Lucia, Alejandro; Pitsiladis, Yannis; Pushkarev, Vladimir; Dyatlov, Dmitry; Orekhov, Evgeniy; Artioli, Guilherme; Guilherme, João; Lancha, Antonio; Ginevičienė, Valentina; Cieszczyk, Pawel; Maciejewska-Karlowska, Agnieszka; et al.
Abstract Background To date, studies investigating the association betweenACTN3 R577X andACE I/D gene variants and elite sprint/power performance have been limited by small cohorts from mixed sport disciplines, without quantitative measures of performance.Aim : To examine the association between these variants and sprint time in elite athletes. Methods We collected a total of 555 best personal 100-, 200-, and 400-m times of 346 elite sprinters in a large cohort of elite Caucasian or African origin sprinters from 10 different countries. Sprinters were genotyped forACTN3 R577X andACE ID variants. Results On average, male Caucasian sprinters with theACTN3 577RR or theACE DD genotype had faster best 200-m sprint time than their 577XX (21.19 ± 0.53 s vs. 21.86 ± 0.54 s, p  = 0.016) andACE II (21.33 ± 0.56 vs. 21.93 ± 0.67 sec, p  = 0.004) counterparts and only one case ofACE II, and no cases ofACTN3 577XX, had a faster 200-m time than the 2012 London Olympics qualifying (vs. 12 qualified sprinters with 577RR or 577RX genotype). Caucasian sprinters with theACE DD genotype had faster best 400-m sprint time than theirACE II counterparts (46.94 ± 1.19 s vs. 48.50 ± 1.07 s, p  = 0.003). Using genetic models we found that theACTN3 577R allele andACE D allele dominant model account for 0.92 % and 1.48 % of sprint time variance, respectively. Conclusions Despite sprint performance relying on many gene variants and environment, the % sprint time variance explained byACE andACTN3 is substantial at the elite level and might be the difference between a world record and only making the final.